Gynecologic surgery during the COVID-19 pandemic: Patan Hospital experience (Journal of Patan Academy of Health Sciences, 2021)
Introduction: The COVID-19 pandemic is a major challenge for health care services including safe and effective surgery. This study aims to analyze gynecological surgery delivery during COVID-19 pandemic.Method:  Data on gynecologic surgeries performed at Patan Hospital from 01 Jan to 31 Dec,2020 during pre-lockdown , lockdown and post-lockdown  period of the COVID-19 pandemic were analyzed from medical record for surgical  procedures, blood transfusion, ICU stay, length of hospital stay, mortality, COVID-19 PCR positive cases. Chi-square and Anova tests were used to compare between three periods, p value